Творчество как механизм адаптации личности к условиям информационного общества - Андреева, А. Ю. (ХНУРЕ, 2019)
The article is devoted to the problem of adaptation of person to the modem information environment. In article adaptation to environment is the major factor promoting maintenance of information-psychological person's safety. The essential role in the course of adaptation is played by psychological factors, especially in connection with the information-communicative processes occurring in a society. The best means of adaptation is the system outlook based on knowledge and directed on association with surrounding world.